An Analysis of the Application of the Principle of Due Diligence in Corporate Criminal Liability in Indonesia - Zendy; Abdul Rasyid Saliman (International Journal of Science and Society, 2026)
The objective of this study is to analyze the legal status of the due diligence principle in determining corporate mens rea and to examine its application in the Indonesian criminal justice system. This study employs a normative legal research method using a legislative, conceptual, and case-based approach through the analysis of sectoral regulations and court decisions. The results of the study indicate that the principle of due diligence does not yet have an explicit legal standing in Indonesian positive law, although it is implicitly recognized in several sectoral regulations as a ground for exculpation or mitigation of liability. Its application by law enforcement officials is severely limited due to the absence of a normative framework, low technical capacity, and a judicial system oriented toward individual accountability. The conclusions of this study recommend legislative reform through implementing regulations of the Criminal Code, the development of technical guidelines for due diligence assessments, and the strengthening of institutional capacity among law enforcement officials.